Does urgent balloon-assisted enteroscopy impact rebleeding and short-term mortality in overt obscure gastrointestinal bleeding?. (2nd October 2020) - Silva, João Carlos; Pinho, Rolando; Ponte, Ana; Rodrigues, Adélia; Rodrigues, Jaime; Gomes, Ana Catarina; Afecto, Edgar; Carvalho, João
Abstract: Background and aims: The diagnostic yield (DY) and therapeutic yield (TY) of balloon-assisted enteroscopy (BAE) in overt obscure gastrointestinal bleeding (OGIB) is higher in the first 72 h. This study aimed to evaluate if this higher DY and TY after urgent BAE impacted the rebleeding rate, time to rebleed and short-term mortality. Methods: Retrospective cohort-study, which consecutively included all patients submitted to BAE for overt OGIB, between 2010 and 2019. Patients were distributed in 2 groups: (1) Urgent BAE; (2) Non-urgent BAE. Rebleeding was defined as an Hb drop >2 g/dL, need for transfusional support or presence of melena/hematochezia. Results: Fifty-four patients were included, of which 17 (31.5%) were submitted to BAE in the first 72 h. DY and TY of urgent BAE (DY 88.2%; n  = 15; TY 94.1%; n  = 16) was higher compared to non-urgent BAE (DY 59.5%; n  = 22; TY 45.9%; n  = 17) (DY p  = .03) (TY p  = .001). The rebleeding rate at 1, 2, and 5 years was 32.0%, 34.0%and 37.0%, respectively. Rebleeding was lower after urgent BAE (17.6%; n  = 3) compared to non-urgent BAE (45.9%; n  = 17) ( p  = .04). Rebleeding tended to occurr earlier in non-urgent BAE, being at 6-months (32.5%) and 36 months (41.3%) ( p  = .05). OGIB related 30-day mortality was 5.4% ( n  = 2) for non-urgent BAE and 0% for urgent BAE ( p  = .5). Conclusion: Urgent BAE might be associated with higher DY and TY with lower rebleeding and trend toward higher rebleeding-free time.